2017
DOI: 10.3233/bme-171673
|View full text |Cite
|
Sign up to set email alerts
|

Tight medial knot tying may increase retearing risk after transosseous equivalent repair of rotator cuff tendon

Abstract: In the knotted TOE repair, tight medial knot tying might cause a high stress concentration around medial knots, which may constitute one of the pathogenetic factors of postoperative retearing at this site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Busfield et al demonstrated that although lateral row knotless fixation has been shown not to sacrifice the structural integrity of this construct, the addition of a knotless medial row compromises the construct leading to greater gapping and failure at lower loads [ 2 ]. In contrast, Sano et al revealed that higher stress concentrations exist around the medial anchor in the double-row fixation, suggesting a biomechanical disadvantage of the medial knot tying [ 18 ]. Taken together, these reports suggest that although medial knot tying offers a biomechanical advantage, a high stress concentration at the tying site affects tendon integrity after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Busfield et al demonstrated that although lateral row knotless fixation has been shown not to sacrifice the structural integrity of this construct, the addition of a knotless medial row compromises the construct leading to greater gapping and failure at lower loads [ 2 ]. In contrast, Sano et al revealed that higher stress concentrations exist around the medial anchor in the double-row fixation, suggesting a biomechanical disadvantage of the medial knot tying [ 18 ]. Taken together, these reports suggest that although medial knot tying offers a biomechanical advantage, a high stress concentration at the tying site affects tendon integrity after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed similar results; however, the number of incompletely healed tendons at the final follow-up was significantly greater in the WMT group than in the WOMT group. Unlike the medial-tying suture bridge, the knotless suture bridge not only restored the pressured footprint, but also reduced the tension overload of the suture-tendon interface in the medial row [ 18 , 19 ]. This reduces the possibility of strangulation and subsequent necrosis of the tendon at the medial row [ 4 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knotless linkage allows equal load sharing across the repair by using the anchors as pulleys to potentiate the strength of repair. 3 , 9 , 10 , 16 , 20 , 24 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…The knotless linkage allows equal load sharing across the repair by using the anchors as pulleys to potentiate the strength of repair. 3,9,10,16,20,24,42 Prior studies utilizing linked medial row anchors have been limited to biomechanical studies and technique papers, making the present study the first to report on clinical outcomes after a linked double-row equivalent rotator cuff repair. There were statistically significant improvements in all PRO scores, with the ASES score significantly improving from 35.5 ± 18.2 preoperatively to 93.4 ± 10.6 postoperatively.…”
Section: Discussionmentioning
confidence: 99%